Land and Housing Occupations in Santiago de Chile, 1978-2000 - Braithwaite-Castillo, S (UNIV CONCEPCION, BIBLIOTECA CENTRAL, 2021)
Land and housing occupations, known in Chile as "tomas", have characterized the "pobladores" movement since the second half of the 20th century. However, the literature indicates that, after the national protests of 1983-1986, these actions have been repeated with less frequency, and have gradually ceased. Through a protest event analysis of the occupations that took place in Santiago between 1978 and 2000, we have shown that these actions have occurred more commonly than thought. Therefore, they could be understood as a part of a unitary period of mobilization for housing. The historical continuity of this form of mobilization throughout very diverse political contexts can be explained because the "tomas" have largely achieved the objective of the homeless: not so much to settle on a plot of land, but rather to cause a public event, in order to start negotiation with the authorities.